1994
DOI: 10.1073/pnas.91.4.1371
|View full text |Cite
|
Sign up to set email alerts
|

Chloride ions catalyze the formation of cis adducts inthe binding of anti-benzo[a]pyrene diol epoxide to nucleicacids.

Abstract: The alkylation of DNA by racemic 7r,8t-dihydroxy-9t,10t-epoxy-7,8,9,10-tetrahydrobenzo[alpyrene (ant-BPDE) exhibits a strong preference for formation of trans adducts between the N2 deoxyguanosine alkylation site and the (+)-enantiomer of anli-BPDE. In the presence of 10 mM buffer with no added salt, 98% of the adducts formed with native calf thymus DNA result from trans opening ofthe epoxide ring. The strong selectivity for trans adduct formation obtained with duplex DNA at low salt concentration is found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…In both yeast and people, these solute carriers are specific to various organic anion molecules including glutathione, sulfate, and glucuronide conjugates, which are the ultimate products of BaP metabolism prior to excretion in humans (Pritchard et al, 2005). Interestingly, other solute carrier families have been implicated in human BaP toxicity, such as SLC38A5 which is thought to indirectly favor cis DNA adduct formation by increasing the chloride ion concentration thus catalyzing S N 2 attack of the BPDE carbocation metabolite (Wolfe et al, 1994). However, literature concerning the role of solute family 22 in human BaP toxicity is limited and warrants further investigation given the potential role played by the orthologous gene in yeast BaP exposure and hydroquinone metabolite toxicity (Keum et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In both yeast and people, these solute carriers are specific to various organic anion molecules including glutathione, sulfate, and glucuronide conjugates, which are the ultimate products of BaP metabolism prior to excretion in humans (Pritchard et al, 2005). Interestingly, other solute carrier families have been implicated in human BaP toxicity, such as SLC38A5 which is thought to indirectly favor cis DNA adduct formation by increasing the chloride ion concentration thus catalyzing S N 2 attack of the BPDE carbocation metabolite (Wolfe et al, 1994). However, literature concerning the role of solute family 22 in human BaP toxicity is limited and warrants further investigation given the potential role played by the orthologous gene in yeast BaP exposure and hydroquinone metabolite toxicity (Keum et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…DNA (14,16,18,19). Initially, we observed that halide ions catalyze the hydrolysis of (()-anti-BPDE (14).…”
Section: Introductionmentioning
confidence: 97%
“…Trans addition of guanine to the C-10 position of (+) and (−)- anti -BPDE produces (+)- trans-N 2 -BPDE-dG and (−)- trans-N 2 -BPDE-dG, while cis addition results in (+) and (−)- cis-N 2 -BPDE-dG isomers ( Scheme 1 ). While trans-N 2 -BPDE-dG adducts are the most common diastereomers in vivo ( 10 ), the cis adducts are preferentially generated under high salt conditions ( 11 , 12 ). Cis and trans N 2 -BPDE-dG have distinct conformations in DNA, which influences their recognition by DNA repair proteins ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%